2000
DOI: 10.1038/35000617
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human guanylate-binding protein 1 representing a unique class of GTP-binding proteins

Abstract: Interferon-gamma is an immunomodulatory substance that induces the expression of many genes to orchestrate a cellular response and establish the antiviral state of the cell. Among the most abundant antiviral proteins induced by interferon-gamma are guanylate-binding proteins such as GBP1 and GBP2. These are large GTP-binding proteins of relative molecular mass 67,000 with a high-turnover GTPase activity and an antiviral effect. Here we have determined the crystal structure of full-length human GBP1 to 1.8 A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
364
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(389 citation statements)
references
References 27 publications
14
364
2
Order By: Relevance
“…The interdomain interactions of Drp1 could be predicted based upon results of the guanylate-binding protein 1 crystal structure and structural studies of the related dynamin and Mx proteins (18,(21)(22)(23). However, to date results for Drp1/Dnm1p results have been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interdomain interactions of Drp1 could be predicted based upon results of the guanylate-binding protein 1 crystal structure and structural studies of the related dynamin and Mx proteins (18,(21)(22)(23). However, to date results for Drp1/Dnm1p results have been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…In dynamin, dimers/tetramers assemble to form rings and collars at the base of clathrin-coated pits, inducing cooperative increases in its GTPase activity (2)(3)(4)(5). Formation of higher order structures and cooperative increases in GTPase activity have also been described for the dynamin-related Mx and guanylate-binding protein families (17)(18)(19)(20). In many cases, detailed analyses have been performed to characterize the domains involved in assembly and cooperative GTPase stimulation of these proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] In particular, based on the crystal structure of GBP-1 20,21 and on biochemical considerations, it was proposed that GBP-1 belongs to the group of large GTP-binding proteins such as Mx and dynamin, all of which have a similar domain composition and GTPase activity, although sequence homology is very low. 20 We have shown that GBP-1 is the key and selective mediator of the anti-proliferative effect of ICs on both microvascular and macrovascular endothelial cells in vitro and that GBP-1 expression was inversely related with cell proliferation in vessel endothelial cells of Kaposi's sarcoma (KS) in vivo. In addition, GBP-1 expression in endothelial cells was found to be highly induced by ICs and inhibited by angiogenic growth factors.…”
Section: During Angiogenesis and Inflammatory Processes Endothelial mentioning
confidence: 99%
“…G uanylate-binding proteins (GBPs) belong to a family of large GTPases that includes dynamins and Mx proteins (1,2). These proteins are characterized by their ability to oligomerize and can display oligomerization-dependent stimulation of GTP hydrolysis (3).…”
mentioning
confidence: 99%